SENJA: KOMPOSISI MUSIK POP SENJA - Pusung, Juaniken Rachel Emmanuella; Suweca, I Wayan; Wiyati, Wahyu Sri (UPT Pusat Penerbitan LP2MPP ISI Denpasar, 2022)
Purpose: In the composition of a pop song entitled Senja, cultivators were inspired to create a pop music composition using the help of MIDI sequencer and audio effect processor. MIDI and Sequencer are two different things but can work together with each other that can be used in the recording process or the production and presentation of a work of music. Research method: The ability to compose ideas and be able to hear audio replayed quickly allows composers to experiment with the files. Results and discussion: Because MIDI is a collection of commands that make sound, MIDI circuits can be manipulated in a variety of ways that audio pre-recordings cannot. Implication: In the process of making this final task, the cultivator decided to pour his personal experience (internal) into a song called Senja. It is applied to a pop music composition played by 5 people (Quintet Performance) with the help of MIDI Sequencer.